The Role of the Notary in Preventing and Overcoming Mistakes in Van Omstandigheden Made by Housing Developers in Home Purchase and Sale Credit Agreements through the Developer - Faizal, Akhmad Bagus (Jurnal Konstatering, 2024)
The implementation of housing credit agreements through housing developers often experiences problems, one of which is fraudulent acts committed by the developer, resulting in losses for both housing buyers and the bank as the loan fund provider. The type of legal research used is non-doctrinal. In this non-doctrinal legal research, law is conceptualized as a manifestation of the symbolic meanings of social actors as seen in the interactions between them. That the real reality of life does not exist in the empirical realm which is also the observational realm, it does not appear in the form of behavior that is patterned and structured objectively (let alone normative) and therefore can be measured to produce quantitative data. The reality of life actually only exists in the realm of meaning which appears in the form of symbols which can only be understood after being interpreted. Such a reality cannot be easily "captured" through external observation and measurement. Based on the research conducted, it was found that Notaries have also increasingly become mediators in disputes related to notarial matters, including the issue of agreements for the use of building construction services, this is a development of the authority of Notaries as Notary legal instructors. In its development, this does not yet have legal certainty considering that the UUJN does not expressly state that a mediator is one of the authorities of a Notary, however, the UUJN also does not contain a prohibition on a Notary becoming a mediator, and it is common knowledge that a mediator is also not a position that is included in the State Civil Apparatus. The absence of clear regulations regarding the notary's position as a mediator means that the notary's position as a mediator in notarial disputes does not have a clear legal basis. So the role of the Notary also does not have legality in deciding the mediation of a failure to build dispute, or the results of the Notary's mediation in cases of fraud committed by housing developers in housing sale and purchase agreements through KPR credit.